Investigating Health Technology Diffusion in New Zealand – How Does it Spread and Who Stands to Gain? - Louise Allsopp (New Zealand Government, The Treasury, 2006)
Previous Treasury research has identified "price and coverage" effects as playing a key role in the growth of historical health expenditure. This incorporates factors such as technological change and input prices including wages. Bryant et. al. (2004) found that between 1950-51 and 2001-02, growth in price and coverage effects was the main source of long run growth in government health expenditure and has accounted for 3-4% growth per year since the early 1990s. This paper explores how a new health technology diffuses across District Health Boards (DHBs), the price and coverage effects, and whether access is evenly spread across the population i.e. who benefits from a new device or procedure. In particular, it highlights: the variation in clinical practice between different DHBs the degree to which the adoption of a particular technology in one DHB impacts on neighbouring DHBs: - a "domino" effect occurs when the adoption of a technology in one DHB leads to other DHBs following suit - the adoption of a technology in one DHB leads to increased inter-district flows between DHBs. differences in access between geographical regions and also ethnic groups The paper takes the example of a new procedure used in coronary care known as `stenting' and examines its adoption across the different DHBs. Data used pertains to different heart procedures adopted across New Zealand over a particular time frame (1995-2004). It comprises patient details plus information relating to the DHB in which the procedure was carried out and also the patient's domicile DHB.
Keywords: I11; O33; 330; technology diffusion; coronary procedures; health expenditure